Practical management of sudden cardiac arrest on the football field. Issue 16 (3rd August 2012) - Kramer, Efraim Benjamin; Botha, Martin; Drezner, Jonathan; Abdelrahman, Yasser; Dvorak, Jiri
Abstract : Sudden cardiac arrest (SCA) remains a tragic occurrence on the football field. The limits of preparticipation cardiovascular screening make it compulsory that prearranged emergency medical services be available at all football matches to immediately respond to any collapsed player. Management of SCA involves prompt recognition, immediate cardiopulmonary resuscitation (CPR) and early defibrillation. Any football player who collapses without contact with another player or obstacle should be regarded as being in SCA until proven otherwise. An automated external defibrillator (AED), or manual defibrillator if an AED is not available, should be immediately accessible on the field during competitions. This study presents guidelines for a practical and systematic approach to the management of SCA on the football field.